The Evaluation of Vocational High School Practice Room Infrastructure for Beauty Department Based on Curriculum Needs - Maghfiroh, Anik; Sudana, I Made; Syamwil, Rodia (Universitas Negeri Semarang, 2019)
The unemployment of vocational high school (SMK) graduates at the moment is ranked at the top of 9.27% of 131.55 million people working force. This is because the limitation of facilities and infrastructures that exist in the practice room in vocational high School (SMK) so that it is the cause of low-power graduates in the workforce.Ã‚Â This research aims to know: (1) The condition of the infrastructure facilities of SMK majoring in beauty department in the district of Jepara, (2) the level of conformity of infrastructure to the minimum standard Permendiknas number 40 year 2008, and (3) the adequacy of the infrastructure to the requirements of the curriculum. This research is an evaluation study with a discrepansi evaluation model. The approach used is a quantitative descriptive with percentage analysis. Data collection techniques using interview analysis, documents and observations. The analytical techniques used are descriptive statistics. The results showed that: (1) condition of facilities and infrastructures of vocational space competency of beauty department in Jepara District 50.6% with sufficient criteria decent. (2) The level of conformity of facilities and infrastructures of the practice room of 56.2% with adequate criteria appropriate (3) the adequacy of the facility of the practice room infrastructure to the needs of curriculum 45.11% with sufficient criteria meet.